A new state's debut in regional diplomacy: Namibia and the Southern Africa Development Community (SADC). Issue 1 (2nd January 2017) - Mushelenga, Peya; van Wyk, Jo-Ansie
ABSTRACT: The Republic of Namibia has been one of the last states in southern Africa to gain independence. As a newly independent state, Namibia formulated a regional foreign policy-based on historical support and relations. One arena where Namibia made its diplomatic debut was in a multilateral context through its engagement with the Southern African Development Community (SADC) and its predecessor, the Southern African Development Coordination Conference (SADCC). Building on the parallels in Namibia and SADC's relations, Namibia has transformed itself into a leading country in the region through various diplomatic practices typically used by new states. As s a newly independent or new state, the case of Namibia's regional diplomacy in respect of SADC offers some insights into new state diplomacy. Firstly, Namibia's regional diplomacy reflects some continuity in the liberation movements' relations with regional actors. In the second instance, regional diplomacy offers new states a relatively safe environment to develop its diplomatic confidence. Thirdly, Namibia's regional diplomacy reiterates the importance of diplomatic skill, technical expertise and bureaucratic experience, which, in the fourth instance, can be translated into credible organizational and diplomatic innovation in the region.